A little learning - Tesh, Jane (Tesh, Jane. Madeline Maclin mystery., 2009)
"Former beauty queen and fledgling private investigator Madeline Maclin, has married her best friend, Jerry Fairweather, and settled into his old house in the small town of Celosia, North Carolina...And now Madeline is involved in the mysterious death of Amelia Lever, an unpopular teacher at Celosia Elementary School...And then there's Maddy's latest case. Nathan Fenton has hired her to help solve a riddle left to him by his Uncle Elijah, a man who loved to play games..."--Dust jacket.